English language reading culture among primary school students in Terengganu - Mohd Nazri bin Latiff Azmi (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
In this study, the researcher focuses on the main element of literacy which is reading. This exploratory study examines the English language reading culture among primary school students in Terengganu. For this study, reading culture is defined as the summation of all the attitudes that have become habits due to many related factors. The study examines four issues related to reading culture in Terengganu. Among them are: first, reading habits; second, reading strategies; third, reading interventions and finally language policy. The researcher obtained data from various sources: reading assessment, questionnaires, semi-structured-interviews and document study. The sample included 1820 students and 346 teachers throughout Terengganu. The students were not only asked to answer questionnaires but also sat for an established reading assessment called. The San Diego Quick Reading' assessment. Meanwhile, teachers were given a questionnaire comprising a set of a Likert-scale and open-ended questions. The views of 11 experts were also incorporated on this issue. Besides that, students' English performance records throughout the year were also scrutinized in order to fulfill the objectives of the study. The findings of the study reveal that students' reading ability is low; added to that is the revelation that reading culture only moderately exists in schools. There is almost a non-existent reading culture in most homes. On a positive note, both students and teachers feel that parents can create a true English reading environment for the students.